Physical Activity, Cognition, and Brain Outcomes: A Review of the 2018 Physical Activity Guidelines - Erickson, Kirk I; Hillman, Charles; Stillman, Chelsea M; Ballard, Rachel M; Bloodgood, Bonny; Conroy, David E; Macko, Richard; Marquez, David X; Petruzzello, Steven J; Powell, Kenneth E (Medicine and science in sports and exercise, 2019)
Physical activity (PA) is known to improve cognitive and brain function, but debate continues regarding the consistency and magnitude of its effects, populations and cognitive domains most affected, and parameters necessary to achieve the greatest improvements (e.g., dose). In this umbrella review conducted in part for the 2018 Health and Human Services Physical Activity Guidelines for Americans Advisory Committee, we examined whether PA interventions enhance cognitive and brain outcomes across the life span, as well as in populations experiencing cognitive dysfunction (e.g., schizophrenia). Systematic reviews, meta-analyses, and pooled analyses were used. We further examined whether engaging in greater amounts of PA is associated with a reduced risk of developing cognitive impairment and dementia in late adulthood. Moderate evidence from randomized controlled trials indicates an association between moderate- to vigorous-intensity PA and improvements in cognition, including performance on academic achievement and neuropsychological tests, such as those measuring processing speed, memory, and executive function. Strong evidence demonstrates that acute bouts of moderate- to vigorous-intensity PA have transient benefits for cognition during the postrecovery period after exercise. Strong evidence demonstrates that greater amounts of PA are associated with a reduced risk of developing cognitive impairment, including Alzheimer's disease. The strength of the findings varies across the life span and in individuals with medical conditions influencing cognition. There is moderate-to-strong support that PA benefits cognitive functioning during early and late periods of the life span and in certain populations characterized by cognitive deficits.